The Potency of Antidiabetic of Psidium guajava Fruit Extract Against Streptozotocin-induced Type 2 Diabetic Rats - Citagami, Safira Salsabila; Ruliff, Saninah Candrawati (Universitas Airlangga, 2024)
Background: The chronic disease known as diabetes mellitus is brought on by either the pancreas's inability to make enough insulin or the body's inability to use it. Purpose: This plant finds applications for treating diarrhea, dysentery, gastroenteritis, hypertension, diabetes, caries and pain relief. Purpose: The current study aimed to determine how Psidium guajava fruit extract affected the blood glucose, body weights, and insulin levels of streptozotocin (STZ)-induced diabetic rats over 21 days. Methods: The extract's effectiveness was compared to that of glibenclamide, a common hypoglycemic medication. 30 male Wistar albino rats were divided into 5 groups with 6 animals in each group. V: Normal control (Group-I), diabetic control (Group-II), diabetic rats treated with glibenclamide 0.6mg/kg bw (Group-III), diabetic rats treated with Psidium guajava fruit extract 200 mg/kg bw (Group-IV) and Psidium guajava fruit extract 400 mg/kg bw (Group-V). All group of rats were subjected to evaluation of body weight, blood glucose and serum insulin levels on day 0, 7, 14 and 21 of the experiment. Results: There was significant (P<0.05) decrease in body weight and serum insulin and significant (P<0.05) increase in blood glucose level in Group-II compared to Group-I rats. In the Present study, daily oral administration of Psidium guajava fruit extract at dose rate of 200 and 400 mg/kg bw and glibenclamide at 0.6mg/kg bw in diabetic rats for 21 days showed a progressive improvement in body weight, blood glucose and serum insulin concentration. Conclusion: It can therefore be concluded the results of this study indicate that Psidium guajava fruit extract possesses anti-diabetic properties in Wistar albino rats.